Analysis of internal control monitoring for tax management inefficiencies - Diah Rizkyan Dewi (Keynesia : International Journal of Economy and Business, 2023)
Tax payment efficiency results from the company's success in tax management. Efficiency or inefficiency occurs in the estuary of a series of procedures that constitute the internal control process within the company. Tax Control is a form of supervisory action whether the implementation or implementation is following the company's planning. The action referred to here is a series of procedures carried out for supervision. So internal control is attached to tax control to create efficiency. This research focuses on the strength or weakness of internal control over the implementation of tax obligations, especially on VAT of PT CTA. This research is a follow-up research from previous research that assesses the efficiency of VAT payments at PT CTA. This study analyzes the internal control of the company's VAT management. The analysis results show the company's internal control weakness using the COSO internal control measurement tool in managing VAT. Strong internal control will be able to minimize the potential for tax costs or minimize inefficiencies in tax payments.